Innovative Leadership of School Administrators under the Patumthani Primary Educational Service Area Office 1 - Khemtong, Sittisak; ชวศิริกุลฑล, นันทนา; รักษนคร, กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to 1) examine the level of innovative leadership among school administrators 2) compare the innovative leadership of school administrators as classified by position status, educational level, work experience, and school size and 3) investigate guidelines for the development of innovative leadership among school administrators under Pathumthani Primary Educational Service Area Office 1. The sample consisted of 334 participants, including school administrators and teachers. The sample size was determined using Yamane’s formula (Yamane, 1967). Stratified random sampling was employed, with school size used as the stratum, followed by simple random sampling through lottery selection. The research instrument was a five-point rating scale questionnaire, with an Index of Item-Objective Congruence (IOC) ranging from 0.60-1 and a reliability coefficient of .98. The statistics used for data analysis included frequency, percentage, mean, standard deviation, t-test, and F-test. When differences in variance were found, pairwise comparisons were conducted using Scheffé’s method. Content analysis was also applied to qualitative data.           The research findings revealed that• The overall and dimensional levels of innovative leadership among school administrators was at a high level.• In comparing the innovative leadership of school administrators, differences in position status showed no significant difference overall. Differences in educational level showed a statistically significant difference overall at the .01 level. Differences based on experience showed no significant difference overall or in any dimension. Differences based on school size showed a statistically significant difference overall at the .01 level.• The guidelines for developing innovative leadership among school administrators under Pathumthani Primary Educational Service Area Office 1 suggest that administrators should establish a clear vision aligned with the context of change, promote participation and teamwork, develop creative thinking skills and the systematic application of innovation, and create an organizational climate conducive to learning and innovation. These approaches aim to enhance the quality of learners.